An overview of nutritional profiling in foods: Bioanalytical techniques and useful protocols - Mondal, Deb Duhita; Chakraborty, Ushashi; Bera, Manotosh; Ghosh, Subhrojyoti; Kar, Debasish (Frontiers in Nutrition, 2023)
Maintaining a nutritious diet is essential for humans if they want to live healthier. Several food businesses and food safety organizations play a significant role and offer useful ways for improving nutritional quality that assists consumers in making informed selections. Making poor food choices and consuming unhealthy meals are the main causes of non-communicable diseases. Using nutritional profile models, it is possible to evaluate the nutritional value, calorie content, and amount of micro and macronutrients contained in a given food accompanied by additional details on the nutrition anomaly provided by published standard nutrients and nutrient databases. To construct an ideal nutritional model that can facilitate food consumption, analytical methods such as chromatography, microscopy, assays, and metabolomics can be applied. In this review, we are focusing on the different analytical techniques and the various protocols of nutritional profiling and their application and refinement of the models.